2017
DOI: 10.1093/dote/dox098
|View full text |Cite
|
Sign up to set email alerts
|

Fully robotic da Vinci Ivor–Lewis esophagectomy in four-arm technique—problems and solutions

Abstract: The aim of this technical note is a step-by-step description of a fully robotic abdominothoracic esophagectomy with an intrathoracic esophagogastrostomy. We report on our technique and short-term results of 75 patients undergoing an Ivor-Lewis esophagectomy using a fully robotic 4-arm approach in the abdominal and thoracic phase with a hand-sewn intrathoracic anastomosis. There are several important steps and differences to consider compared to the conventional minimal invasive approach (patient's positioning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Conversion to open procedure occurred in two (2.6%) patients in the abdominal and 14 patients (18.7%) in the thoracic phase. Main reasons for conversion were problems during lifting of the gastric conduit and difficulties in the construction of the esophagogastrostomy . In Japan, however, Nakauchi et al reported on the initiation in 2009 of robotic gastrectomy and esophagectomy for patients with upper gastrointestinal cancer, and they showed potential advantages of the da Vinci Surgical System in reducing postoperative local complications after gastrectomy and recurrent laryngeal nerve palsy after esophagectomy.…”
Section: Treatmentsmentioning
confidence: 99%
“…Conversion to open procedure occurred in two (2.6%) patients in the abdominal and 14 patients (18.7%) in the thoracic phase. Main reasons for conversion were problems during lifting of the gastric conduit and difficulties in the construction of the esophagogastrostomy . In Japan, however, Nakauchi et al reported on the initiation in 2009 of robotic gastrectomy and esophagectomy for patients with upper gastrointestinal cancer, and they showed potential advantages of the da Vinci Surgical System in reducing postoperative local complications after gastrectomy and recurrent laryngeal nerve palsy after esophagectomy.…”
Section: Treatmentsmentioning
confidence: 99%
“…By translating the surgeon's natural hand movements on the console to the surgical instruments with endo-wrists, a robotic system can achieve a large range of motion that enables manual suturing. Several case series have been published, which suggest that a robot-assisted hand-sewn intrathoracic anastomosis is safe and feasible for RAMIE (39)(40)(41). Prospective randomized studies are warranted to investigate hand-sewing versus stapling in terms of anastomotic leakage and benign stricture formation after RAMIE with an intrathoracic anastomosis.…”
Section: Anastomotic Technique In Ramiementioning
confidence: 99%
“…Three human cadaver models were used for this feasibility study in an institutional review board (IRB) approved clinical lab. The abdominal part has been described in previous publications and can be performed with similar techniques [1,2], using either a multiport (da Vinci XI) or a single port approach with two assistant trocars (da Vinci SP).…”
Section: Procedures Set Upmentioning
confidence: 99%